Studi Perbandingan Kuat Geser Tanah Lempung Lunak Yang Distabilisasi Dengan Kolom Kapur Dan Kolom Campuran Pasir Kapur - Malikhi, Imam; , Agus Susanto, S.T., M.T; , Anto Budi Listyawan, S.T., M.Sc (2016)
Soil from Troketon Vilage, Pedan Sub-district, Klaten District, Indonesia is soft clay soil with high plasticity (Merdhiyanto, 2015). This soil condition cause the pavement around that area is easily to be wavy and holey, and also cause cracks on the building wall because of excessive and non-uniform soil settlement. One of method to overcome this problem is to do stabilization by combining the two methods, the method of vertical drainage and chemical methods. In this study, to determine the effect of stabilization with vertical drainage methods and chemical methods against the soft clay soil of the Troketon Village, Pedan Sub-district, Klaten District is by comparing stabilization using lime columns and sand-lime mixture columns. Comparison between these two types of tests is observed on shear strength parameters, they are cohesion (C) and the inside friction angle of the soil (o). The results shows that the value of cohesion (C) from the origin soil is 0.1417 kg/cm2, it improves after stabilized by the lime column and sand-lime mixture column. Stabilization with lime column has a value of cohesion (C) of 0.5393 kg/cm2. Sand-lime mixture column has a value of cohesion (C) of 0.3402 kg/cm2. Value of inside friction angle of origin soil is 1.81°, also increasing after it is stabilized by lime column and sand-lime mixture columns. Stabilization with lime column has a value of inside friction angle of soil 5.96°, and stabilization with sand-lime mixture column has a value 5.07°. The highest shear stress on stabilization using lime column is equal to 0.725 kg/cm2, better than the shear stress on stabilization using sand-lime mixture column 0.490 kg/cm2. While shear stress for origin soil is 0,191 kg/cm2. Therefore, the stabilization with lime columns is more effective than the stabilization with sand-lime mixture column.